M-aminobenzene sulfonic acid covalent bond double-bonded polyaniline and carboxyl carbon fiber bundle material as well as preparation method and application thereof

By using m-aminobenzenesulfonic acid bridge molecules, polyaniline and carboxy carbon fibers are connected by covalent bonding of amide and sulfonamide to form polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundle material, the problem of polyaniline falling off during cyclic charge and discharge is solved, and electrode materials with high stability and high electrochemical performance are achieved.

CN119877274APending Publication Date: 2025-04-25SOUTHEAST UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311380481.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Among the existing polyaniline-p-phenylenediamine-oxygenated carbon fiber array electrode materials, the hydrogen bond between polyaniline and p-phenylenediamine is weak, resulting in the polyaniline being easily shedded during cyclic charging and discharge, affecting the stability of electrochemical energy storage.

Method used

Meta-aminobenzenesulfonic acid is used as a bridge molecule, and polyaniline and carboxy carbon fiber are connected by covalent bonds of amide and sulfonamide to form polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundle material to achieve a balanced reinforcement of the molecular structure with strong interface effects.

Benefits of technology

It significantly improves the stability of the polyaniline molecular structure and electrochemical cycling stability, enhances the electrochemical capacitance performance and cyclic capacitance retention, and is suitable for energy storage applications of fully flexible supercapacitors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877274A_ABST
    Figure CN119877274A_ABST
Patent Text Reader

Abstract

The invention discloses an m-aminobenzene sulfonic acid covalent bond double-bonded polyaniline and carboxyl carbon fiber bundle material and a preparation method and energy storage application thereof.The carboxyl carbon fiber bundle is synthesized through a hydrothermal oxidation method to serve as a base material, and then m-aminobenzene sulfonic acid-carboxyl carbon fibers bonded through amide covalent bonds are synthesized through an organic solvent thermal grafting method; then, electroactive polyaniline is introduced by adopting an electrochemical polymerization deposition method, polyaniline-m-aminobenzene sulfonic acid bonded by sulfonamide covalent bonds is synthesized, a polyaniline-m-aminobenzene sulfonic acid-carboxyl carbon fiber bundle material with a covalent bond double bond structure is prepared, m-aminobenzene sulfonic acid molecules are connected with carboxyl carbon fibers through amide covalent bonds, and the carboxyl carbon fibers are bonded through carboxyl carbon fibers. Meanwhile, sulfamide covalent bonds are connected with polyaniline to form a covalent bond double bond interface balance strengthening structure integrated material, meanwhile, intermolecular connection is strengthened, charge transfer resistance is reduced, and structural stability and cycling stability are improved. The material is used for constructing a carbon fiber-based flexible supercapacitor, and full-flexible energy storage is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a meta-aminobenzenesulfonic acid covalent bond double bonded polyaniline and carboxyl carbon fiber bundle material and a preparation method and electrochemical energy storage application thereof, belonging to the field of new materials and new energy. Background Art

[0002] Pseudocapacitor supercapacitors are based on the rapid reversible Faraday reaction on the surface and near the surface of electrode materials, and have the advantages of fast charging and discharging, long cycle life, wide operating temperature, high power density, etc. Supercapacitors can replace traditional batteries; they can also be combined with various batteries to form hybrid power systems, and have a variety of application scenarios.

[0003] Supercapacitor electrode materials include carbon, polymers and metal oxides. In electrochemical energy storage systems, carbon fibers have excellent flexibility and high conductivity characteristics, and can be used as electrode current collectors and electrode matrices. Conductive polymers such as polyaniline with high theoretical specific capacitance characteristics can be used as electrode active materials, and the mutual interface between carbon fibers and polyaniline electroactive materials is a key factor affecting the electrochemical capacitance performance. These interface regions affect the electrochemical performance due to poor adhesion between the fiber matrix and the polymer material. The continuous expansion and contraction of polyaniline during the cyclic charge and discharge process causes its polymer chain to break and become inactive. It is very important to compound polyaniline with carbon fibers to enhance the structural stability of the molecule. The current technical solution is mainly to construct a polyaniline / carbon fiber composite electrode material with a physical interface or a chemical interface, and the chemical interface is better than the physical interface. The prior art proposes to use a bifunctional small molecule p-phenylenediamine as a bridging molecule to simultaneously connect polyaniline and carbon fibers, and to construct a p-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material. This electrode material can improve the electrochemical capacitance performance to a certain extent. However, p-phenylenediamine molecules can only form a chemical bond strengthening interface with strong interaction with carbon fiber, while p-phenylenediamine molecules cannot form a chemical bond strengthening interface with polyaniline, but only a hydrogen bond weak interaction interface. The phenylenediamine molecules form this kind of unbalanced interaction with carbon fiber and polyaniline respectively, which affects the stability of the molecular structure of the composite electrode material. During the continuous cycle charge and discharge process, polyaniline based on the hydrogen bond weak interaction interface is easy to fall off from the surface of polyaniline-p-phenylenediamine-oxygen-containing carbon fiber array electrode material. The key technical problems of the molecular structure stability and electrochemical cycle stability of the composite of p-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material have not been fundamentally solved. Therefore, it is necessary to develop materials with more stable structure and electrochemical cycle to solve the problem of electrochemical energy storage stability of polyaniline and carbon fiber array composite electrodes. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the prior art, a polyaniline-carbon fiber electrode material is constructed by a p-phenylenediamine bridging molecule. The hydrogen bonding between p-phenylenediamine and polyaniline is much weaker than the chemical bonding between p-phenylenediamine and carbon fiber. During the cyclic charge and discharge process of the electrode material, the polyaniline based on the weak interface effect is easy to fall off from the surface of the composite electrode material matrix, and the electrochemical energy storage stability of this type of polyaniline composite electrode is not ideal. The first purpose of the present invention is to provide a m-aminobenzenesulfonic acid covalent bond double bonded polyaniline and carboxyl carbon fiber (briefly described as polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle material, the bridging molecule m-aminobenzenesulfonic acid and the polyaniline molecule and the carbon fiber matrix are both connected by strong chemical bonds. The balanced strengthening molecular stable structure solves the problem of interface unbalanced strengthening molecular structure existing in the prior art about polyaniline-p-phenylenediamine-oxygen-containing carbon fiber electrode materials. This double-interface double chemical bond strengthened balanced structure solves the problems of polyaniline molecular structure stability and electrochemical cycle stability, and the electrochemical capacitance performance, cycle capacitance retention rate, and rate capacitance retention rate can be greatly improved. The electrode material has both high specific capacitance and charge-discharge cycle stability and can be better suitable for energy storage applications in fully flexible supercapacitors; the second purpose of the present invention is to provide a method for preparing the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material; the third purpose of the present invention is to provide the application of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material in constructing a weavable and wearable flexible linear supercapacitor to achieve fully flexible energy storage.

[0005] Technical solution: To achieve the above-mentioned purpose of the invention, the present invention discloses a m-aminobenzenesulfonic acid covalently doubly bonded polyaniline and carboxyl carbon fiber (abbreviated as polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle material, comprising a carboxyl carbon fiber bundle, m-aminobenzenesulfonic acid and polyaniline; the m-aminobenzenesulfonic acid is bonded to the carboxyl carbon fiber bundle with an amide covalent bond, and is simultaneously bonded to the polyaniline with a sulfonamide covalent bond, to form a m-aminobenzenesulfonic acid covalently doubly bonded polyaniline and carboxyl carbon fiber (abbreviated as polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle material.

[0006] Among them, the amino group and sulfonic acid functional group of the m-aminobenzenesulfonic acid as a bridging molecule are respectively connected to the polyaniline and the carboxyl carbon fiber bundle by covalent double bonding, and an amide covalent bonding interface is formed between the carboxyl carbon fiber bundle and the m-aminobenzenesulfonic acid, and a sulfonamide covalent bonding interface is formed between the polyaniline and the m-aminobenzenesulfonic acid, forming a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material. Among them, the surface of the carboxyl carbon fiber bundle contains a carboxylic acid functional group; the bridging molecule m-aminobenzenesulfonic acid has an amino group and a sulfonic acid double functional group, and the amino functional group at one end of the m-aminobenzenesulfonic acid forms an amide covalent bond with the carboxylic acid functional group of the carboxyl carbon fiber bundle; the sulfonic acid functional group at the other end of the m-aminobenzenesulfonic acid forms a sulfonamide covalent bond with the amino functional group of the polyaniline, and the bridging molecule m-aminobenzenesulfonic acid simultaneously connects the carboxyl carbon fiber bundle and the polyaniline by chemical covalent bonding, and the interface is connected by different covalent double bonding, forming an integrated material with a covalent double bonding interface and a balanced strengthening molecular bridging structure.

[0007] The carboxyl carbon fiber bundle is composed of directional and tightly stacked fiber bundles with an ordered array structure, and the diameter of the fiber bundle is 8-9 μm; the fiber bundle is composed of 80-100 nanofibers, and the diameter of the nanofibers is 70-90 nm; the polyaniline has a cross-linked nanocolumn structure, and the diameter of the polyaniline nanocolumn is 50-80 nm.

[0008] A molecular model of a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material according to the present invention, wherein the molecular model of the carboxyl carbon fiber bundle is described by a carboxyl graphite carbon molecule, wherein the carboxyl graphite carbon molecule comprises a carboxylic acid functional group, and the carboxylic acid group is distributed at the edge of a hexagonal parallel ring of a graphite carbon plane; the molecular model of the polyaniline is in the form of a dimer; the molecular model of the m-aminobenzenesulfonic acid is that an amino group at one end of the m-aminobenzenesulfonic acid is covalently bonded to the carboxyl graphite carbon via an amide group, and a sulfonic acid group at the other end of the m-aminobenzenesulfonic acid is covalently bonded to a polyaniline molecule via a sulfonamide, thereby constructing a three-component molecular model of a covalent double-bonded interface balanced reinforcement molecular structure of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material.

[0009] Among them, the molecular model of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material is optimized and calculated based on the density functional theory of the first principles, and the optimized three-component molecular structure of the double-bonded balanced reinforcement structure is obtained, and the intermolecular distance and intermolecular angle are obtained.

[0010] There is an amide covalent bond between the carboxyl functional group of the carboxyl carbon fiber bundle and the amino functional group of m-aminobenzenesulfonic acid, and the CN bond length is There is an amide covalent bond between the carboxyl carbon fiber bundle and the m-aminobenzenesulfonic acid molecule, and the angle between the six-membered ring of the carboxyl carbon fiber and the benzene ring of m-aminobenzenesulfonic acid is 12°; the SN bond length between the imino functional group of the polyaniline and the amino functional group of m-aminobenzenesulfonic acid is There is a sulfonamide covalent bond between the polyaniline and m-aminobenzenesulfonic acid molecules, and the angle between the adjacent benzene rings of the polyaniline and the benzene rings of m-aminobenzenesulfonic acid is 86°.

[0011] Among them, according to the charge distribution, in the polyaniline-carboxy carbon fiber bundle, the distribution charges of carboxy carbon fiber and polyaniline molecules are 0.120e and -0.190e respectively, and in the polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundle, the distribution charges of carboxy carbon fiber and polyaniline molecules are -0.034e and 0.106e respectively. The polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundle forms a π-π hyperconjugated molecular structure, which enhances electron delocalization, promotes charge transfer, and improves electronic conductivity.

[0012] Among them, it is obtained from the electrostatic potential distribution that for the polyaniline-carboxyl carbon fiber bundle, the negative potential of the carboxyl carbon fiber is mainly located on the carbon main chain and the amide oxygen atom, and the positive potential of the carboxyl carbon fiber is mainly distributed on the hydrogen atom. The negative potential of the polyaniline molecule is mainly distributed on the nitrogen atom and the benzene ring. The positive potential of polyaniline is mainly distributed on the hydrogen atom. For the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle, the charge delocalization is enhanced, which is conducive to charge transfer. The area of ​​the negative potential zone on the carbon main chain is reduced and becomes an electrically neutral zone. This is because the carboxyl carbon fiber and polyaniline are connected by the bridge molecule m-aminobenzenesulfonic acid, forming an extended delocalized π-π hyperconjugated system, the electron cloud distribution tends to be uniform, and there is an electrostatic potential overlap area between m-aminobenzenesulfonic acid, polyaniline and carboxyl carbon fiber, forming a double covalent bond between sulfonamide and amide.

[0013] The method for preparing the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material of the present invention comprises the following steps:

[0014] A. Using a hydrothermal oxidation method, a carbon fiber bundle is used as a precursor to prepare a carboxyl carbon fiber bundle;

[0015] B. Using an organic solvent thermal grafting method, with carboxyl carbon fiber bundles as the substrate, N,N'-dicyclohexylcarbodiimide as the reaction dehydrating agent, and m-aminobenzenesulfonic acid as the bridging molecule, m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber (abbreviated as m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundles were prepared;

[0016] C. The electrochemical polymerization deposition method is adopted, with m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle as the substrate, monomer molecule aniline is added, and sulfuric acid is used as the protonic acid dopant to prepare polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material.

[0017] Wherein, in step (1), the hydrothermal oxidation method comprises the following steps: ultrasonically treating the carbon fiber bundle in an anhydrous ethanol solution, using a mass fraction of 55%-70% nitric acid-70% H2SO4 mixed acid solution as the reaction medium, the oxidizing mixed acid can promote the surface of the carbon fiber to be fully oxidized to generate carboxylic acid functional groups, using a hydrothermal oxidation method for deep oxidation treatment, the oxidation reaction temperature is 80-110°C, the oxidation reaction time is 10-18h, washing and drying, thermal activation treatment under inert gas, the thermal activation treatment temperature is 400-650°C, the thermal activation treatment time is 3-6h, and a carboxyl carbon fiber bundle is obtained through a hydrothermal oxidation-thermal oxidation method.

[0018] Among them, in step (2), the organic solvent thermal grafting method includes the following steps: preparing a 0.01-0.02M m-aminobenzenesulfonic acid solution as a reaction solution, immersing the carboxyl carbon fiber bundle in the above reaction solution, and conducting an organic solvent thermal (amidation) reaction at a temperature of 100-130°C for a reaction time of 5-7h, then cooling to room temperature, washing and drying, to obtain a m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber (referred to as m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle.

[0019] Wherein, in step (3), the electrochemical polymerization deposition method comprises the following steps: using m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode, respectively, to establish a three-electrode reaction system, configuring a reaction solution containing 1.2M sulfuric acid and 0.2-0.4M aniline aqueous solution, with a potential window of -0.2V to 0.8V and a scanning rate of 5-20mV s -1 , the scanning time is 20-30min, and the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material is obtained.

[0020] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material described in the present invention is used in constructing a weavable and wearable flexible linear supercapacitor to achieve fully flexible energy storage.

[0021] The flexible linear supercapacitor is composed of a positive electrode, a negative electrode, a gel polymer electrolyte, a porous diaphragm and a packaging film. The gel polymer electrolyte is coated on the positive electrode and the negative electrode, and then the positive electrode and the negative electrode are separated by a porous diaphragm, wound into a spiral shape, and then packaged with a packaging film to form a flexible linear supercapacitor. The flexible linear supercapacitor is fixed on the flexible fabric of clothes or backpacks by weaving to construct a weavable and wearable flexible linear supercapacitor for full flexible energy storage applications.

[0022] The specific process of the application includes: using the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material as a self-supporting electrode and directly applying it to the positive electrode and the negative electrode.

[0023] The gel polymer electrolyte is a composite of polyvinyl alcohol, sulfuric acid and water, the porous separator is a polypropylene non-woven fabric, and the packaging film is an elastic silicone rubber film.

[0024] The preparation method of the gel polymer electrolyte comprises the following steps: weighing 1g of polyvinyl alcohol into a flask, adding 5-20mL of distilled water, stirring continuously at a constant temperature of 85-95°C until the polyvinyl alcohol is completely dissolved, then adding 5-10mL of 1M sulfuric acid dropwise into the flask, stirring thoroughly to form a homogeneous state, and then maintaining stirring for 2-4h to evaporate excess water to finally obtain a gel polymer electrolyte.

[0025] The gel polymer electrolyte has an optimized component ratio, and the ratio of sulfuric acid, polyvinyl alcohol and water is 1.2-1.6:1:10.

[0026] Among them, the rated operating voltage of the weavable and wearable flexible linear supercapacitor is 1.8V, and it can operate normally by stable cyclic charging and discharging in a bent and folded state.

[0027] Among them, the specific capacitance of the flexible linear supercapacitor in the bent and folded state reaches 88.50F g -1 , the energy density reaches 39.83Wh kg -1 , 2A g -1 The capacity retention rate after 2000 charge and discharge cycles is 78.1%.

[0028] The invention provides a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material, comprising a matrix material carboxyl carbon fiber bundle, a bridging molecule m-aminobenzenesulfonic acid and an electroactive material polyaniline, wherein one end amino group of m-aminobenzenesulfonic acid is connected to the carboxyl group of the carboxyl carbon fiber bundle to form an amide covalent bond, and the other end sulfonic acid group is connected to the polyaniline to form a sulfonamide covalent bond. The m-aminobenzenesulfonic acid bridging molecule covalently bonds the polyaniline and the carboxyl carbon fiber bundle to form a strong interface effect, and the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material strengthens the stability of the polyaniline molecular structure. The surface of the carboxyl carbon fiber bundle matrix is ​​rough and maintains a longitudinally arranged structure. The aminobenzenesulfonic acid covalently double-bonded polyaniline and the carboxyl carbon fiber bundle material can provide more active sites for the deposition of polyaniline. At the same time, one end amino group of m-aminobenzenesulfonic acid is connected to the carboxyl group of the carboxyl carbon fiber bundle to form an amide bond, and the other end amino group is connected to the polyaniline amino group to form a sulfonamide covalent bond. The m-aminobenzenesulfonic acid bridging molecule simultaneously connects polyaniline and carboxyl carbon fiber bundles with different covalent bonds to construct a strong interface effect, forming a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material with a bridging structure, which reduces the interface resistance and improves the charge transfer efficiency, thereby improving the specific capacitance performance and structural stability of the material. The bridging structure feature solves the problem of polyaniline's continuous expansion and contraction during the charge and discharge process, resulting in reduced structural stability, improves its charge and discharge cycle stability, solves the problem of polyaniline falling off the surface of the carboxyl carbon fiber bundle matrix during the charge and discharge process, and further improves the specific capacity. An electrode material with high conductivity and high structural stability is formed.

[0029] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material of the present invention has both high electrical conductivity and specific surface area of ​​carbon fiber bundles and high electrochemical activity and electrical conductivity of polyaniline. The amino group and sulfonic acid functional groups of m-aminobenzenesulfonic acid are respectively covalently double-bonded to polyaniline and carboxyl carbon fiber bundles to form an integrated structure. One side amino group of m-aminobenzenesulfonic acid is connected to the carboxyl group of the carboxyl carbon fiber bundle to form an amide covalent bond, and the other side sulfonic acid group is connected to polyaniline to form a sulfonamide covalent bond. The formation of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material strengthens the stability of the molecular structure of polyaniline. The m-aminobenzenesulfonic acid bridging molecule connects polyaniline and carboxyl carbon fiber bundles with sulfonamide covalent bonds and amide covalent bonds, respectively, to improve the stability of the material structure, and it can be used as a supercapacitor electrode material for electrochemical efficient energy storage.

[0030] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material of the present invention forms a supercapacitor electrode material by connecting polyaniline with sulfonamide covalent bonds through bridging molecules of m-aminobenzenesulfonic acid and connecting carboxyl carbon fiber bundles with amide covalent bonds, thereby realizing electrochemical energy storage. The presence of the carboxyl carbon fiber bundle matrix provides favorable support for polyaniline, and m-aminobenzenesulfonic acid reinforces the structure of polyaniline nanocolumns, thereby slowing down the degree of structural collapse of the electrode material during the charge and discharge process. The cycle stability of the electrode material is enhanced.

[0031] In order to strengthen the interface connection, the present invention introduces a bifunctional bridging molecule m-aminobenzenesulfonic acid with a structure similar to that of an aniline monomer between polyaniline and a carboxyl carbon fiber bundle, and the m-aminobenzenesulfonic acid amino group and the sulfonic acid functional group respectively connect the polyaniline and the carboxyl carbon fiber bundle to form an integrated structure. One side terminal amino group of the intermediate aminobenzenesulfonic acid of the present invention connects with the carboxyl group of the carboxyl carbon fiber bundle to form an amide bond, and the other side terminal sulfonic acid group connects with the polyaniline to form a sulfonamide covalent bond. The m-aminobenzenesulfonic acid bridging molecule co-connects the polyaniline and the carboxyl carbon fiber bundle to form a strong interface effect to form a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material with a bridging structure, strengthens the stability of the polyaniline molecular structure, reduces the interface resistance, improves the charge transfer, and thus improves the specific capacitance of the material. At the same time, the phenomenon of irreversible attenuation of the capacitance caused by excessive volume expansion / contraction of the polyaniline electrode material during the electrolyte ion insertion / extraction process is solved, and its charge and discharge cycle stability performance is improved.

[0032] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0033] (1) The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared by the present invention has a covalent double-bonded interface balanced strengthening molecular structure, and has the characteristics of both high conductivity and high molecular structure stability, which can effectively improve the structural stability of the electrode material, and has high specific capacitance and good cycle stability. Among them, the carboxyl carbon fiber bundle has high conductivity and provides a matrix for the electroactive material, and the m-aminobenzenesulfonic acid bridging molecule co-connects the polyaniline and the carboxyl carbon fiber bundle to form a bridging structure with strong interface action, thereby strengthening the stability of the polyaniline molecular structure.

[0034] (2) The preparation process of the present invention is simple and convenient. The prepared polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material can be applied to flexible, weavable, wearable supercapacitor electrodes, construct energy storage devices, and realize electrochemical energy storage applications, which has very good prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic structural diagram of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material of the present invention;

[0036] Figure 2The present invention is a process flow chart for preparing the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material;

[0037] Figure 3 This is a field emission scanning electron microscope image of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared in Example 1;

[0038] Figure 4 The Fourier transform infrared spectrum and X-ray photoelectron spectrum of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared in Example 1;

[0039] Figure 5 The electrochemical performance test diagrams of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles are shown;

[0040] Figure 6 Electrochemical impedance spectroscopy of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles;

[0041] Figure 7 Electrochemical cyclic voltammetry curves and electrochemical constant current charge-discharge curves of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles;

[0042] Figure 8 This is a diagram of theoretical calculation results of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material;

[0043] Fig. 9 This is a graph showing the performance test results of a weavable and wearable flexible linear supercapacitor. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0045] Example 1 Preparation of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material

[0046] The preparation process of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material is as follows Figure 2 As shown, 5 is a carbon fiber bundle, 6 is an m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle, (I) is a hydrothermal oxidation method, (II) is an organic solvent thermal grafting method. (III) is an electrochemical polymerization deposition method. m-aminobenzenesulfonic acid is connected to the carboxyl carbon fiber bundle by an amide covalent bond, and is connected to polyaniline by a sulfonamide covalent bond, forming a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle integrated structural material with a covalent double bond interface balanced strengthening molecular structure.

[0047] (1) Synthesis of carboxyl carbon fiber bundles

[0048] Hydrothermal oxidation method I was used: First, 30 mg of carbon fiber bundle 5 was ultrasonically treated in 50 mL of anhydrous ethanol solution for 2 h, and the carbon fiber bundle was treated with 50 mL of a mixed acid solution of 65% nitric acid-70% sulfuric acid as the reaction medium. The oxidizing mixed acid can promote the full oxidation of the carbon fiber surface to generate carboxylic acid functional groups. Hydrothermal oxidation method I was used for oxidation treatment, the reaction temperature was 95 ° C, the reaction time was 14 h, and the obtained sample was washed with deionized water and dried at 60 ° C for 12 h. Then, thermal activation treatment was carried out in an argon atmosphere, and the heating rate was 5 ° C min -1 , maintaining the temperature at 620°C, the reaction time being 4h, the carbon fiber bundle treated by hydrothermal oxidation formed a rough surface, and obtained the carboxyl carbon fiber bundle 1 (abbreviated as ACF).

[0049] (2) Synthesis of m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles

[0050] Organic solvent thermal grafting method (II): Dimethylformamide is used as the organic reaction solvent, and a 0.17M solution of m-aminobenzenesulfonic acid and 0.05M dicyclohexylcarbodiimide (as a dehydrating agent) are prepared as 50mL of the reaction solution. The carboxyl carbon fiber bundle 1 is immersed in the above reaction solution and subjected to an organic solvent thermal reaction at a reaction temperature of 150°C for 12 hours. The mixture is then cooled to room temperature, washed and dried to obtain a m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle 6 (abbreviated as ACF-mABSM).

[0051] (3) Synthesis of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles

[0052] Electrochemical polymerization deposition method (III): Use m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle 6 as the working electrode, platinum sheet as the counter electrode, and saturated calomel electrode as the reference electrode to establish a three-electrode reaction system, prepare 50 ml of 1.0 M sulfuric acid and 0.1 M aniline aqueous solution as the reaction solution, take 10 mg of m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle 6 and immerse it in the above 50 mL reaction solution, use cyclic voltammetry, the potential window is -0.2 V ~ 1.0 V, and the scan rate is 25 mVs -1 The number of cycles was 15. The working electrode after the reaction was washed with distilled water and ethanol until it was neutral, and then placed in an oven at 50°C for 12 hours to obtain polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material 4 (abbreviated as ACF-mABSM-PANI).

[0053] The structural schematic diagram of the obtained polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material 4 is as follows Figure 1As shown, 1 is a carboxyl carbon fiber bundle, 2 is m-aminobenzenesulfonic acid, 3 is polyaniline, δ is an amide covalent bond, and β is a sulfonamide covalent bond. Polyaniline 3 and m-aminobenzenesulfonic acid 2 are connected through a sulfonamide covalent bond β, and the carboxyl carbon fiber bundle 1 and m-aminobenzenesulfonic acid 2 are connected through an amide covalent bond δ, forming a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material 4.

[0054] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared in Example 1 was characterized by morphology and structure (field emission scanning electron microscope analysis). The results are as follows: Figure 3 shown. Figure 3 The field emission scanning electron microscope images of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared in Example 1, wherein (a) is a scanning electron microscope image of a carboxyl carbon fiber bundle, (b) is a scanning electron microscope image of a m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber (abbreviated as m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle, (c) is a scanning electron microscope image of a polyaniline covalently bonded carboxyl carbon fiber (abbreviated as polyaniline-carboxyl carbon fiber) bundle, and (d) is a scanning electron microscope image of a m-aminobenzenesulfonic acid covalently doubly bonded polyaniline and carboxyl carbon fiber (abbreviated as polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber) bundle. Figure 3 It can be seen that the carboxyl carbon fiber bundle is composed of oriented and tightly packed fiber bundles, with an ordered array structure, a fiber bundle diameter of 8-9μm, and a fiber bundle composed of 80-100 nanofibers, with a nanofiber diameter of 70-80nm. The m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle has many m-aminobenzenesulfonic acid nanoparticles on the surface, providing more active sites for the nucleation and growth of polyaniline. The surface of the polyaniline covalently bonded carboxyl carbon fiber bundle has a large number of polyaniline nanocolumns. The surface of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material has cross-linked nanocolumn structure polyaniline, forming a three-dimensional structure, and the diameter of the polyaniline nanocolumn is 60-80nm; the m-aminobenzenesulfonic acid nanoparticles on the surface of the carboxyl carbon fiber bundle serve as nucleation sites for the growth of polyaniline, which is conducive to the formation of tightly connected polyaniline nanocolumns and promotes the interfacial electron transfer between polyaniline and carboxyl carbon fiber bundles.

[0055] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material 4 prepared in Example 1 was characterized by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The results are as follows Figure 4 shown. Figure 4 The Fourier transform infrared spectrum and X-ray photoelectron spectrum of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material prepared in Example 1, wherein (a) is the Fourier transform infrared spectrum of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material, (b) is the total spectrum of the X-ray photoelectron spectrum, (c) is the O1S spectrum of the X-ray photoelectron spectrum, and (d) is the N1s spectrum of the X-ray photoelectron spectrum. Figure 4As can be seen in (a), the wavelengths at 3435, 1385 and 1094 cm -1 The characteristic peaks correspond to the OH stretching vibration peak, OH bending vibration peak, and CO stretching vibration peak of carboxyl carbon fiber. Located at 1627cm -1 The characteristic peaks correspond to the C=O stretching vibration peak of the carboxylic acid group of the carboxyl carbon fiber and the C=C stretching vibration peak of graphite; for the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material, the peak is located at 3435cm -1 The characteristic peaks correspond to the superimposed stretching vibration peaks of OH and NH; in addition, the peak at 1235 cm -1 With 605cm -1 The characteristic peaks correspond to the CN stretching vibration peak and the NH out-of-plane bending vibration peak; located at 1737cm -1 ,1323cm -1 ,1173cm -1 ,847cm -1 With 574cm -1 The characteristic peaks correspond to the C=O stretching vibration peak, the O=S=O asymmetric stretching vibration peak, the O=S=O symmetric stretching vibration peak, the CS stretching vibration peak and the O=S=O shear vibration peak, indicating the formation of a sulfonamide bond. -1 With 1737cm -1 The characteristic peaks correspond to the CN stretching vibration peak and the C=O stretching vibration peak, respectively, indicating the formation of an amide bond. Therefore, the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material contains an amide bond -CO-NH- and a sulfonamide bond -SO2-NH-. Figure 4 (b)-(d) are visible, the total spectrum contains O, N, C, S elements; the S2p spectrum contains -SO2-N<(168.3eV), The N 1s spectrum contains the energy spectrum peaks of three chemically bound states of S: -SO2-NH-(401.0eV), -CO-NH-(399.5eV)and -NH2(398.8eV). In summary, the amino functional group at one end of m-aminobenzenesulfonic acid forms an amide covalent bond with the carboxyl functional group of the carboxyl carbon fiber bundle; the amino functional group at the other end of m-aminobenzenesulfonic acid forms a sulfonamide covalent bond with polyaniline to form a bridging structure.

[0056] Example 2 Electrochemical Performance Test

[0057] By adopting steps (1) and (3) in Example 1, the carboxyl carbon fiber material is directly used as the working electrode to prepare a polyaniline-carboxyl carbon fiber bundle material (abbreviated as ACF-PANI).

[0058] The polyaniline-carboxyl carbon fiber bundle material prepared in this embodiment and the carboxyl carbon fiber bundle, aminobenzenesulfonic acid-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials prepared in Example 1 were tested for electrochemical properties. 10 mg of carboxyl carbon fiber bundle, 11 mg of m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle, 12 mg of polyaniline-carboxyl carbon fiber bundle and 13 mg of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle were taken as working electrodes, platinum sheet was taken as counter electrode, saturated calomel electrode was taken as reference electrode, 50 mL of 1.0 M sulfuric acid solution was taken as reaction electrolyte, and cyclic voltammetry was used to measure electrochemical properties. The results are as follows: Figure 5-6 shown.

[0059] Figure 5 The electrochemical performance test diagrams of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles are shown in Figure 1. (a) is the cyclic voltammetry curve at a scan rate of 5 mV s-1, and (b) is the current density of 0.5 A g -1 (c) is the constant current charge and discharge test curve at different current densities of 0.5-2.5A g -1 (d) is the relationship between specific capacity and current density when the current density is 2A. -1 Cyclic charge and discharge stability curve.

[0060] like Figure 5 (a) Cyclic voltammetry curve, the potential range was set to -0.2-0.6 V, and the scan rate was 5 mV s -1 The current density response and closed curve integral area of ​​the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material are significantly larger than those of other materials. According to the specific capacitance formula calculated by the cyclic voltammetry curve, the specific capacitance values ​​of the carboxyl carbon fiber bundle, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle, polyaniline-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials are 25.8 F g -1 , 38.8F g -1 , 313.0F g -1 and 548.1F g -1 Compared with the p-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material (CN116779339A) invented by us earlier, the specific capacitance value is 403.75F g -1 The specific capacitance value of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material (548.1F g -1 ) is significantly improved, thus showing its higher current density response and specific capacitance performance.

[0061] like Figure 5(b) The electrochemical constant current charge-discharge curve is shown, with the potential range set to -0.2-0.6 V and the current density set to 0.5 A g -1 The specific capacitance values ​​calculated by constant current charge and discharge of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles, and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles were 20.5Fg -1 , 38.9F g -1 , 335.0F g -1 With 599.3F g -1 Compared with the p-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material (CN116779339A) invented by us earlier, the specific capacitance value is 437.5F g -1 The specific capacitance value of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material (599.3F g -1 ) is significantly improved. The constant current charge-discharge test and the cyclic voltammetry test maintain basically the same specific capacitance results and size order, which also shows that the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material has excellent conductivity and electroactivity, thus giving it higher electrochemical capacitance performance.

[0062] like Figure 5 (c) shows the carbon fiber bundles of carboxyl, m-aminobenzenesulfonic acid-carboxyl, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles at different current densities of 0.5-2.5 A g -1 The specific capacitance performance curve under the conditions. When the current density increases from 0.5 to 2.5A -1 When the specific capacity retention rate was 62.08%, 49.41%, 89.37% and 90.37%, respectively. Therefore, the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material exhibits higher specific capacitance performance and rate performance. The bridging molecule m-aminobenzenesulfonic acid makes the connection between polyaniline and carboxyl carbon fiber bundles tighter, reduces the interface resistance, improves the charge transfer, and thus improves the specific capacitance of the material, achieving an enhanced energy storage effect.

[0063] like Figure 5 (d) shows the cyclic charge-discharge stability curves of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles, and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles. The current density of constant current charge and discharge is set to 2A g -1, the cycle number is 2000 times, and the corresponding specific capacitance retention rates are 81.1%, 92.6%, 54.4% and 93.8% respectively; the specific capacitance retention rates of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material are 93.8% and 87.2% for 2000 and 5000 cycles respectively. Compared with the p-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material (CN116779339A) invented by us earlier, its specific capacitance retention rate after 2000 cycles is 72.3%. The cyclic charge and discharge stability of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material of the present invention is significantly higher than that of other modified carbon fiber bundle materials, which is substantially improved. Meta-aminobenzenesulfonic acid connects polyaniline and carboxyl carbon fiber bundles with sulfonamide covalent bonds and amide covalent bonds to improve the stability of the molecular structure and avoid structural collapse. Polyaniline nanocolumns form a bridging structure through meta-aminobenzenesulfonic acid to solve the problem of reduced structural stability caused by the continuous expansion and contraction of polyaniline during the charge and discharge process. The interfacial double bond reaction improves the structural stability and improves its charge and discharge cycle stability.

[0064] Figure 6 These are AC impedance spectra of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxy carbon fiber bundles, polyaniline-carboxy carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundles; wherein (a) is the Nyquist diagram of the corresponding electrode material, (b) is the capacitance-frequency diagram of the corresponding electrode material, and (c) is the equivalent circuit diagram of the corresponding electrode material. Figure 6 (ab) shows the AC impedance spectra of carboxyl carbon fiber bundle, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle, polyaniline-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle in 1.0M sulfuric acid solution with a frequency scanning range of 100kHz-10mHz. The AC impedance spectra of the four electrode materials are linearly distributed in the low frequency range and semicircularly distributed in the high frequency range. By fitting and analyzing the electrochemical AC impedance spectra of the electrode materials, the fitting results of the equivalent circuit components are obtained, as shown in Table 1.

[0065] Table 1 Fitting data of equivalent circuit components of different electrode materials

[0066]

[0067]

[0068] As can be seen from Table 1, in the electrochemical reaction process, compared with the carboxyl carbon fiber bundle, the m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle and the polyaniline composite carboxyl carbon fiber bundle material, the m-aminobenzenesulfonic acid bridged polyaniline and the carboxyl carbon fiber bundle obtained the lowest ohmic resistance (R o ) is 2.05Ω, reflecting its better electronic conductivity; the lowest interfacial electron transfer resistance (Rct ) is 0.75Ω, reflecting its better interfacial charge transfer performance; in the low frequency range, the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material obtains a smaller Weber diffusion impedance of W R (0.81881), reflecting its better ion diffusion coefficient; the smaller relaxation time τ0 (46.0s) is obtained, reflecting its better electrochemical reaction kinetics rate performance. In summary, the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material exhibits higher electrochemical capacitance performance than polyaniline composite carboxyl carbon fiber bundle, m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle and carboxyl carbon fiber bundle.

[0069] The polyaniline-carboxyl carbon fiber bundle material prepared in this embodiment and the carboxyl carbon fiber bundle, aminobenzenesulfonic acid-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials prepared in Example 1 were subjected to electrochemical cyclic voltammetry performance tests and electrochemical constant current charge and discharge performance tests. The results are as follows: Figure 7 shown. Figure 7 The electrochemical cyclic voltammetry curves and electrochemical constant current charge-discharge curves of carboxyl carbon fiber bundles, m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, polyaniline-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles are shown in Figure 1, wherein (a) is an electrochemical cyclic voltammetry curve and (b) is an electrochemical constant current charge-discharge curve. Figure 7 As shown in (a), m-aminobenzenesulfonic acid bridged polyaniline and carboxyl carbon fiber bundle 13 mg were used as working electrodes, platinum sheet was used as counter electrode, saturated calomel electrode was used as reference electrode, volume was 50 mL 1.0 M sulfuric acid electrolyte, potential range was set to -0.2-0.6 V, scan rate range was 5-25 mV s -1 ,from Figure 7 As can be seen in (a), the similar shape of the cyclic voltammetry curve shows that the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material has excellent reversibility. In addition, with the increase of the scan rate, the potential shift of the anodic peak and the cathodic peak increases, indicating that the Faraday reaction is gradually affected by the diffusion process. Figure 7 As shown in (b), at a current density of 0.5A g -1 Up to 2.5A g -1 When the constant current charge and discharge curve maintains a good linear symmetry characteristic, it shows that the electrode material has good electrochemical reaction reversibility and coulombic efficiency in the constant current charge and discharge process.

[0070] Example 3

[0071] Molecular models were established for the carboxyl carbon fiber bundle, aminobenzenesulfonic acid-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials prepared in Example 1, and theoretical simulation calculations were performed based on the density functional theory of the first principles. The results are as follows: Figure 8 shown. Figure 8 The figures are the theoretical calculation results of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials; among them, (a) is the molecular model diagram of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials after calculation optimization; (b) is the electrostatic potential distribution diagram of polyaniline-carboxyl carbon fiber and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials; (c) is the charge population distribution diagram of aniline-carboxyl carbon fiber and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials; (d) molecular structure model, HOMO energy band, LUMO energy band, and HOMO-LUMO energy level diagram of aniline-carboxyl carbon fiber and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials.

[0072] Figure 8 (a) The optimized structural molecular models of m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials are shown. The molecular model of carboxyl carbon fiber bundles includes carboxylic acid functional groups, and the carboxylic acid groups are distributed on the edges of the hexagonal rings of the graphite carbon plane. The molecular model of polyaniline is in the form of a dimer. The molecular model of m-aminobenzenesulfonic acid is that the amino group at one end of m-aminobenzenesulfonic acid is covalently bonded to the carboxyl carbon fiber bundle via an amide group, and the amino group at the other end of m-aminobenzenesulfonic acid is covalently bonded to the polyaniline molecule via a sulfonamide bond, thus constructing a three-component molecular model of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material. The carboxyl functional group of the carboxyl carbon fiber bundle forms an amide covalent bond with the amino functional group of m-aminobenzenesulfonic acid, and the CN bond length is There is an amide covalent bond between the carboxyl carbon fiber bundle and the m-aminobenzenesulfonic acid molecule. The six-membered ring of the carboxyl carbon fiber forms an angle of 12° with the benzene ring of m-aminobenzenesulfonic acid. The S-N bond length between the imino functional group of polyaniline and the amino functional group of m-aminobenzenesulfonic acid is There is a sulfonamide covalent bond between polyaniline and m-aminobenzenesulfonic acid molecules, and the adjacent benzene rings of polyaniline and the benzene rings of m-aminobenzenesulfonic acid form an angle of 86°.

[0073] Figure 8(b) shows the electrostatic potential distribution of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles and polyaniline-carboxyl carbon fiber bundles. For polyaniline-carboxyl carbon fiber bundles, the negative potential of carboxyl carbon fiber is mainly located on the carbon main chain and amide oxygen atoms. The positive potential of carboxyl carbon fiber is mainly distributed on hydrogen atoms. The negative potential of polyaniline molecules is mainly distributed on nitrogen atoms and benzene rings. The positive potential of polyaniline is mainly distributed on hydrogen atoms. For polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, charge delocalization is enhanced, which is conducive to charge transfer. The area of ​​the negative potential zone on the carbon main chain is reduced and becomes an electrically neutral zone. This is because the carboxyl carbon fiber and polyaniline are connected by the bridge molecule intermethylaminobenzenesulfonic acid to form an extended delocalized π-π hyperconjugated system. The electron cloud distribution tends to be uniform. There is an electrostatic potential overlap area between m-aminobenzenesulfonic acid, polyaniline and carboxyl carbon fiber, forming a double covalent bond between sulfonamide and amide.

[0074] Figure 8 (c) shows the charge distribution of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles and polyaniline-carboxyl carbon fiber bundles. For polyaniline-carboxyl carbon fiber bundles, the charge distribution of carboxyl carbon fiber and polyaniline molecule is 0.120e and -0.190e, respectively. For polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles, the charge distribution of carboxyl carbon fiber and polyaniline molecule is -0.034e and 0.106e, respectively, which indicates that electrons migrate from polyaniline to carboxyl carbon fiber and the electron cloud distribution tends to be uniform. Comparative analysis shows that the strong interfacial chemical bond interaction in polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles promotes electron migration, and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles form a π-π hyperconjugated molecular structure, which enhances electron delocalization, promotes charge transfer, and improves electronic conductivity.

[0075] The electrochemical test results of Example 2 show that only carboxyl carbon fiber has electronic conductivity in the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material, while polyaniline and m-aminobenzenesulfonic acid do not have electronic conductivity. The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material has a lower ohmic resistance than the carboxyl carbon fiber and exhibits higher electronic conductivity. The present invention obtains an optimized structural molecular model of the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material, which has an extended π-π hyperconjugated molecular structure. The simulation calculation results show that the material of the present invention has a higher electronic conductivity than the carboxyl carbon fiber bundle material, providing a theoretical basis for the technical solution of the present invention.

[0076] Figure 8(d) shows the molecular structure model, HOMO energy band, LUMO energy band, and HOMO-LUMO energy level of carboxyl carbon fiber, m-aminobenzenesulfonic acid-carboxyl carbon fiber, and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber. The HOMO and LUMO energy bands of carboxyl carbon fiber and m-aminobenzenesulfonic acid-carboxyl carbon fiber vary slightly, and m-aminobenzenesulfonic acid has little effect on the energy band of carboxyl carbon fiber. Polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber has a π-π hyperconjugated delocalized structure.

[0077] In the extended delocalized π-π hyperconjugated system of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber, the distribution of HOMO and LUMO are closer to m-aminobenzenesulfonic acid and no longer concentrated on the carboxyl carbon fiber molecules, indicating that the electron distribution has changed. Another important parameter, HOMO-LUMO energy level, obtained from the HOMO and LUMO orbital energy bands, can be used to obtain its chemical reactivity and kinetic stability. The HOMO-LUMO energy level (0.9688eV) of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber is smaller than that of carboxyl carbon fiber (1.3324eV) and m-aminobenzenesulfonic acid-carboxyl carbon fiber (1.2771eV), and the ability of electrons to jump from occupied orbits to empty orbits is enhanced, which has higher electronic conductivity, indicating that the reaction activity of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber is higher than that of carboxyl carbon fiber and m-aminobenzenesulfonic acid-carboxyl carbon fiber.

[0078] The polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material obtained by the present invention has a lower HOMO-LUMO energy level than carboxyl carbon fiber and m-aminobenzenesulfonic acid-carboxyl carbon fiber. The simulation calculation results show that the material of the present invention has higher electrical activity and capacitance performance than the carboxyl carbon fiber bundle material, providing a theoretical basis for the technical solution of the present invention.

[0079] Example 4

[0080] The carboxyl carbon fiber bundle, aminobenzenesulfonic acid-carboxyl carbon fiber bundle and polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle materials prepared in Example 1 were used to construct a weavable and wearable flexible linear supercapacitor, and its electrochemical performance was tested. For details, see Fig. 9 .

[0081] Preparation method of gel polymer electrolyte: weigh 1g of polyvinyl alcohol into a flask, add distilled water, and continue stirring at a constant temperature of 85-95°C until the polyvinyl alcohol is completely dissolved, then add 1M sulfuric acid dropwise into the flask, stir thoroughly to form a homogeneous state, then keep stirring for 3 hours, evaporate excess water, and finally obtain a gel polymer electrolyte; optimize the component ratio of the gel polymer electrolyte, the mass ratio of sulfuric acid, polyvinyl alcohol and water is 1.4:1:10, and a sulfuric acid-polyvinyl alcohol gel polymer electrolyte is obtained.

[0082] The flexible linear supercapacitor is composed of polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles as positive and negative electrodes, sulfuric acid-polyvinyl alcohol gel as polymer gel electrolyte, microporous polypropylene non-woven fabric as porous diaphragm, and elastic silicone rubber film as packaging film. The gel polymer electrolyte is coated on the positive electrode and the negative electrode, and then the positive electrode and the negative electrode are separated by the porous diaphragm, wound into a spiral shape, and then packaged with a packaging film to form a flexible linear supercapacitor. The flexible linear supercapacitor is fixed on the flexible fabric of clothes or backpacks by weaving to construct a weavable and wearable flexible linear supercapacitor for fully flexible energy storage applications. The results are as follows Fig. 9 shown.

[0083] Fig. 9 The performance test results of the weavable and wearable flexible linear supercapacitor are shown in Figure 1, where (a) is the working application diagram; (b) is the cyclic voltammetry curve; (c) is the constant current charge and discharge performance curve; and (d) is the cyclic charge and discharge stability curve.

[0084] Fig. 9 (a) shows the schematic diagram of the application of a weavable and wearable flexible linear supercapacitor, showing its different working states of plane, folding and bending. Polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles are directly applied to the positive electrode and negative electrode as self-supporting electrodes, sulfuric acid-polyvinyl alcohol gel is the polymer gel electrolyte, microporous polypropylene non-woven fabric is the porous diaphragm, the gel polymer electrolyte positive electrode material, the porous diaphragm, and the gel polymer electrolyte negative electrode material are sequentially wrapped and coated, and the elastic silicone rubber film is encapsulated to form a weavable and wearable flexible linear supercapacitor for full flexible energy storage applications. A flexible linear supercapacitor unit can independently drive a light-emitting diode lamp.

[0085] Fig. 9 (b) shows the cyclic voltammetry and constant current charge-discharge performance test curves of the flexible linear supercapacitor. The working electrolyte is 1.0M sulfuric acid solution, and the potential window range is 0-1.8V. The rated working voltage of the flexible linear supercapacitor is 1.8V, and the scan rate is 5-70mV s -1 When the scan rate increases, the cyclic voltammetry curve has a pair of redox peaks, which are attributed to the redox reaction of polyaniline. The current response increases with the increase of the scan rate, showing good rate capacitance performance. The current density is 1-5A g -1 Cyclic charge-discharge curves, specific capacitance is 88.50-11.11 F g -1 , energy density is 39.83-5.00Wh kg -1 The material described in the present invention has good flexible energy storage performance.

[0086] Fig. 9(c) shows the cyclic charge-discharge stability curve of the flexible linear supercapacitor. The current density is 2A g -1 The capacity retention rate was 78.1% after 2000 charge and discharge cycles under the same conditions. The shape and integrated area of ​​the cyclic voltammetry curve before and after 2000 charge and discharge cycles at a scan rate of 50 mV s-1 only changed slightly, proving that the flexible linear supercapacitor has good cycle stability.

[0087] Example 5

[0088] The same preparation method and parameter conditions as in Example 1 were adopted, except that: in step (2), the m-aminobenzenesulfonic acid-carboxyl carbon fiber bundles were synthesized, and the added dicyclohexylcarbodiimide was 0M, 0.001M and 0.1M respectively. The results showed that when 0M of dicyclohexylcarbodiimide was added, the target product polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material was not obtained; the verification result of the target product polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material with 0.001M of dicyclohexylcarbodiimide was not obvious; when 0.1M of dicyclohexylcarbodiimide was added, other by-products were detected instead of the target product polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material. The above results show that the dehydrating agent is a reaction material that must be used in the synthesis preparation step of the present invention, and its dosage is an important factor in the synthesis of the product, and the best effect is only when 0.05M is added.

[0089] Comparative Example 1

[0090] The invention is compared with the prior art regarding the synthesis method of the bridge molecule-bonded polyaniline and carbon fiber bundle material.

[0091] The existing technology adopts surface grafting synthesis method + electrochemical in-situ polymerization method (see CN116779339A). The surface grafting synthesis method adopts hydrothermal synthesis technology, and the oxygen-containing carbon fiber (including carboxyl, epoxy, and hydroxyl groups) is bridged by the hydrothermal reaction of p-phenylenediamine to obtain a p-phenylenediamine-oxygen-containing carbon fiber bundle material in which the oxygen-containing carbon fiber is covalently bonded; the electrochemical in-situ polymerization method adopts an electrochemical polymerization reaction to form polyaniline, and obtains a polyaniline-p-phenylenediamine-oxygen-containing carbon fiber bundle material in which the polyaniline is hydrogen-bonded.

[0092] When the synthesis method of the prior art is adopted and the meta-aminobenzenesulfonic acid used in the present invention is used as the bridging molecule reaction solution for the hydrothermal synthesis reaction, the meta-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material in which the carboxyl carbon fiber is covalently bonded cannot be obtained. The reason is that in the prior art, p-phenylenediamine has only one abundant amino functional group, and the same type of amino functional group does not affect the interface chemical bonding reaction, and the amidation reaction can be completed under mild hydrothermal reaction conditions. The present invention uses meta-aminobenzenesulfonic acid, and the steric hindrance effect of the sulfonic acid group affects the amide reaction activity of the amino group. Different types of functional group amino groups and sulfonic acid groups greatly affect the amidation and sulfonamidation reactions, inhibiting the formation of the material of the present invention.

[0093] The present invention adopts an organic solvent thermal grafting method + an electrochemical polymerization deposition method. With respect to the organic solvent thermal grafting method, m-aminobenzenesulfonic acid is used as a bridging molecule, N,N-dimethylformamide is used as a reaction organic solvent, and N,N'-dicyclohexylcarbodiimide is used as a reaction dehydrating agent. The carboxyl carbon fiber (mainly comprising a carboxyl group) is bridged by a thermal dehydration reaction of the m-aminobenzenesulfonic acid organic solvent, and the dehydrating agent eliminates the water generated by the reaction to obtain a m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material in which the carboxyl carbon fiber is covalently bonded. With respect to the electrochemical polymerization deposition method, polyaniline is directly covalently bonded to the m-aminobenzenesulfonic acid-carboxyl carbon fiber to obtain a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material.

[0094] Comparing the technology of the present invention with the prior art, it is not inevitable that the carbon fiber is converted from oxygen-containing carbon fiber to carboxyl carbon fiber, it is not inevitable that the bridging molecule is converted from phenylenediamine to m-aminobenzenesulfonic acid, and the unbalanced interface connection structure of covalent bonds and hydrogen bonds is converted into a double covalent bond interface balanced reinforcement structure. Therefore, it is not inevitable that the polyaniline-p-phenylenediamine-oxygen-containing carbon fiber bundle is converted into a polyaniline-m-aminobenzenesulfonic acid-carboxy carbon fiber bundle.

Claims

1. A m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material, characterized in that: The material comprises a carboxyl carbon fiber bundle (1), meta-aminobenzenesulfonic acid (2) and polyaniline (3); the meta-aminobenzenesulfonic acid (2) and the carboxylic acid carbon fiber bundle (1) are bonded by an amide covalent bond (δ), and the meta-aminobenzenesulfonic acid (2) and the polyaniline (3) are bonded by a sulfonamide covalent bond (β), thereby forming a meta-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material (4).

2. The m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: The surface of the carboxyl carbon fiber bundle (1) contains carboxylic acid functional groups; the m-aminobenzenesulfonic acid (2) has amino and sulfonic acid bifunctional groups; the amino functional group at one end of the m-aminobenzenesulfonic acid (2) forms an amide covalent bond (δ) with the carboxylic acid functional group of the carboxyl carbon fiber bundle (1); the sulfonic acid functional group at the other end of the m-aminobenzenesulfonic acid (2) forms a sulfonamide covalent bond (β) with the amino functional group of polyaniline (3); the m-aminobenzenesulfonic acid (2) acts as a bridging molecule and simultaneously connects the carboxyl carbon fiber bundle (1) and the polyaniline (3) by chemical covalent bonding, thereby forming a covalent double-bonded interface balanced reinforcement molecular structure integrated material.

3. The m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: The carboxyl carbon fiber bundle (1) is formed by bundles of fibers that are oriented and tightly packed, the fiber bundles are orderly radially arranged and have an orderly array structure, and the fiber bundles have a diameter of 8-9 μm; the fiber bundles are formed by bundles of 80-100 nanofibers, and the nanofibers have a diameter of 70-80 nm; the polyaniline (3) has a cross-linked nanocolumn structure, and the polyaniline nanocolumn has a diameter of 60-80 nm.

4. A molecular model of the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: The molecular model of the carboxyl carbon fiber bundle (1) is described by a carboxyl graphite carbon molecule, wherein the carboxyl graphite carbon molecule includes a carboxyl functional group, and the carboxyl functional group is distributed at the edge of the hexagonal ring of the graphite carbon molecular model plane; the molecular model of the polyaniline (3) is in the form of a dimer; the molecular model of the m-aminobenzenesulfonic acid (2) is that one end amino group of the m-aminobenzenesulfonic acid is connected to the carboxyl graphite carbon molecule by an amide covalent bond, and the other end amino group of the m-aminobenzenesulfonic acid is connected to the polyaniline molecule by a sulfonamide covalent bond, thereby constructing a molecular model of a covalent double-bonded interface balanced reinforcement molecular structure of a m-polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material (4).

5. The molecular model of the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 4, characterized in that: There is an amide covalent bond between the carboxyl functional group of the carboxyl carbon fiber bundle (1) and the amino functional group of the m-aminobenzenesulfonic acid (2), and the CN bond length is The molecules of the carboxyl carbon fiber bundle (1) and the m-aminobenzenesulfonic acid (2) are connected by an amide covalent bond, and the angle between the six-membered ring of the carboxyl carbon fiber and the benzene ring of the m-aminobenzenesulfonic acid is 12°; the SN bond length between the imino functional group of the polyaniline (3) and the amino functional group of the m-aminobenzenesulfonic acid (2) is There is a sulfonamide covalent bond between the molecules of the polyaniline (3) and the m-aminobenzenesulfonic acid (2), and the angle between the adjacent benzene rings of the polyaniline (3) and the benzene rings of the m-aminobenzenesulfonic acid (2) is 86°; from the charge population distribution, it is obtained that in the polyaniline-carboxyl carbon fiber bundle, the population charges of the carboxyl carbon fiber (1) and the polyaniline (3) molecules are 0.120e and -0.190e respectively, and in the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle (4), the population charges of the carboxyl carbon fiber (1) and the polyaniline (3) molecules are -0.034e and 0.106e respectively, and the polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle (4) forms a π-π hyperconjugated molecular structure.

6. A method for preparing the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A. using a hydrothermal oxidation method (I) with a carbon fiber bundle (5) as a precursor and a nitric acid-sulfuric acid mixed acid solution as an oxidation reaction medium to prepare a carboxyl carbon fiber bundle (1); B. using an organic solvent thermal grafting method (II), with a carboxyl carbon fiber bundle (1) as a substrate, N,N'-dicyclohexylcarbodiimide as a reaction dehydrating agent, and meta-aminobenzenesulfonic acid (2) as a grafting molecule, to prepare a meta-aminobenzenesulfonic acid-carboxyl carbon fiber bundle (6); C. The electrochemical polymerization deposition method (III) is used to prepare a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material (4) by using m-aminobenzenesulfonic acid covalently bonded carboxyl carbon fiber bundle (6) as a substrate, aniline (3) as a reaction monomer, and sulfuric acid as a protonic acid dopant.

7. The method for preparing the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: In step (1), the hydrothermal oxidation method (I) comprises the following steps: ultrasonically treating the carbon fiber bundle (5) in an anhydrous ethanol solution, using a mixed acid solution of 60%-70% nitric acid and 70% sulfuric acid by mass as a reaction medium, performing oxidation treatment by a hydrothermal oxidation method, the oxidation reaction temperature is 80-110°C, the oxidation reaction time is 10-18h, washing and drying, and thermal activation treatment under nitrogen gas, the thermal activation treatment temperature is 400-650°C, and the thermal activation treatment time is 3-6h, to obtain a carboxyl carbon fiber bundle (1).

8. The method for preparing the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: In step (2), the organic solvent thermal grafting method (II) comprises the following steps: using dimethylformamide as an organic reaction solvent, preparing a 0.17M m-aminobenzenesulfonic acid solution and a 0.05M dicyclohexylcarbodiimide solution as a reaction solution, immersing the carboxyl carbon fiber bundle (1) in the above reaction solution, and performing an organic solvent thermal reaction at a reaction temperature of 130-160°C for a reaction time of 10-14h, cooling to room temperature, washing and drying, and obtaining a m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle (6).

9. The method for preparing the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1, characterized in that: In step (3), the electrochemical polymerization deposition method (III) The method comprises the following steps: using m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle (6) as a working electrode, a platinum sheet as a counter electrode, and a saturated calomel electrode as a reference electrode, respectively, to establish a three-electrode reaction system, configuring a reaction solution containing 1.0M sulfuric acid and 0.1-0.2M aniline aqueous solution, a potential window of -0.2V to 1.0V, and a scanning rate of 25mV s -1 , the number of cycles is 15, washing to neutrality and drying to obtain a polyaniline-m-aminobenzenesulfonic acid-carboxyl carbon fiber bundle material (4).

10. An application of the m-aminobenzenesulfonic acid covalently double-bonded polyaniline and carboxyl carbon fiber bundle material according to claim 1 in constructing a weavable and wearable flexible linear supercapacitor to achieve fully flexible energy storage.

Citation Information

Patent Citations

  • P-phenylenediamine bridged polyaniline and oxygen-containing carbon fiber array material as well as preparation method and energy storage application thereof

    CN116779339A